The Influence of Environmental Conditions on Creep Behaviour of Polymer Mortars (Malaysian Journal of Civil Engineering, 2018)
The.re sults of a study on the influence of environmental conditions on the creepbehaviour of polymer mortars are pre sented. The compression creep behaviouris examined on six types of filled epoxy resins systems commonly used in thecon struction industry, using a simple spring-loaded system. The creepbehaviours are examined at WOC and 30Â°C with 45% and 60% RH. The creepbehaviour at laboratory ambient condition is also included. Compressivestrength re sults are also determined.The results indicate that 'the composition of polymer influences the creepbehaviour of polymer mortars. The influence of temperature is more significantthan the humidity on the creep behaviour